Response: On torture, slavery, and resistance - DuBois, Page (Biblical interpretation, 2017)
This response to the essays collected here considers questions of torture, slavery, and resistance. Building on the fruitful extension of earlier work on ancient Greek practices of the basanos, or “touchstone,” and on slavery in the ancient world and in antebellum America, the response takes account of the valuable and thought-provoking use of duBois’ work in the new contexts of early Christianity. The response also points to her recent work on the relationship of torture, crucifixion, slavery, forms of resistance, and the persistence, in new forms, of what Hellenists tend to call “polytheism”.